Empowerment of NU Community Through Business Development of Banana Chips - Hidayat, Khoirul; Prasnowo, M. Adhi; Nurdin, Shafiq; Fathani, Abdul Halim (Proceedings of Annual Conference on Community Engagement, 2018)
Rural Community Cowek majority NU members who always keep the tradition and culture of NU which always makes togetherness and mutual cooperation as well as not to damage the existing tradition in a society which is often called Islamic archipelago. One is cultivated by the community and the results are very abundant in this country are bananas, especially the banana is a fruit of the plant regardless of the season and take place throughout the year and the very easy process of planting. Post-harvest handling processes are often only picked bananas and then directly sold to the consumer either to the village below and Pandaan was stricken with a fairly cheap price. The process of improving the business results of the processed products to increase the selling bananas do with one of them being the manufacture of banana chips produced by the local community, of course, the expected results in the form of processed bananas, banana chips will improve the community economy. The results of dialogue with the people who have does business of making banana chips, agreed efforts to address production constraints primary preferred treatment is a tool for the process of slicing bananas, in this case, to be made is slicer banana mechanically by an electric motor, which aims to make the production process manufacture of banana chips can be increased. The method used in this NU community development activities is the Participatory Rural Appraisal (PRA) is the public involved in this. It started with a discussion with the community in identifying community problems, determining the priority issues that must be resolved. The results of this community empowerment felt by the results in the presence of a banana slicer machine is capable of producing 50 kg/hour, which was previously only 10 kg/hour. In addition to higher yields, the result is also more evenly incision size, and are no longer too thick or too thin as it is today. With the banana, slicer machine can solve the problems of society and can increase turnover and increase their excretion of NU community welfare.